ANALISIS KESESUAIAN LAHAN KOMODITAS UNGGULAN DAN ARAHAN PENGEMBANGANNYA DI WILAYAHKABUPATEN CIANJUR - Wistha Nowar; Dwi Putro Tejo Baskoro; Boedi Tjahjono (Diponegoro University, 2015)
Regional development can be carried out with an emphasis on the basic sectors and leading commodities. The purpose of this study is twofold. The first is to determine the basic sectors, sub-sectors, and leading commodities, and the second is to analyze the suitability and allocation directives of land for leading commodities. The data used include gross regional domestic product (GDP) of West Java and the harvested area in 2011-2013.The other data are land suitability requirement, map soil types, rainfall, temperature, grade slope, erosion, map of soil units, land use, spatial plans, and administrative maps. Location Quotient (LQ) method is used to determine the basic sectors and sub-sectors. Meanwhile, the LQ and Differential Shift and Share are used to determine the leading commodities. The land suitability of leading commodities is spatially analyzed using Geographical Information System (GIS). The results have shown that the agriculture is the basic sector and food crop agriculture is and the basic sub-sector. The leading commodities are soybean, peanut, and rice. The land suitability classes are S2 and S3. The available allocation areas are 27.984 Hectares for wet-field paddy, 17.984 Hectares for peanuts, and 38.835 Hectares for soybean.